Analisis Faktor yang Memengaruhi Keputusan Pedagang Warung Sembako di Desa Waringin Jaya dalam Membayar Zakat Perdagangan - Suhandi, Andi; Nur Iskandar, Dede; Bayu Umara; Enur Hotimah; Novi Yulianti (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
Trade zakat is one of the religious obligations for Muslims who meet certain criteria in commercial activities. However, the level of zakat compliance among small-scale traders remains relatively low, often due to various internal and external factors. This study aims to identify and analyze the factors influencing the decision of grocery store traders in Waringin Jaya Village to pay trade zakat. The research employs a quantitative approach using a field survey method. Primary data were collected through questionnaires with a 5-point Likert scale, distributed to 80 respondents. Secondary data were sourced from relevant literature such as books, journals, and scientific articles. The data were analyzed using validity and reliability tests as well as factor analysis with SPSS software. The results show that religiosity, perception, and motivation are the main factors influencing traders’ decisions. Religiosity was the most dominant factor with a Total Variance Explained of 28.751%. This indicates that traders with strong religious values are more likely to fulfill their zakat obligations. The study highlights the importance of spiritual awareness and community-based religious education in increasing zakat compliance.